2022
DOI: 10.3389/fimmu.2022.880668
|View full text |Cite
|
Sign up to set email alerts
|

FOXO Dictates Initiation of B Cell Development and Myeloid Restriction in Common Lymphoid Progenitors

Abstract: The development of B cells relies on an intricate network of transcription factors critical for developmental progression and lineage commitment. In the B cell developmental trajectory, a temporal switch from predominant Foxo3 to Foxo1 expression occurs at the CLP stage. Utilizing VAV-iCre mediated conditional deletion, we found that the loss of FOXO3 impaired B cell development from LMPP down to B cell precursors, while the loss of FOXO1 impaired B cell commitment and resulted in a complete developmental bloc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…RAG1 and RAG2 are target genes of the transcription factor FOXO1 and inactivation of FOXO1 has been described to reduce expression of RAG1 and RAG2 (Lazorchak et al 2010 ; Lazorchak and Su 2011 ; Benhamou et al 2018 ; Peña-Pérez et al 2022 ). In order to study whether inhibition of FOXO1 also downregulates RAG1 and RAG2 expression in Namalwa cells, they were exposed to increasing concentrations (up to 0.1 µM) of the FOXO1 inhibitor AS1842856 for 6, 24 and 48 h. After exposure to 0.01 and 0.1 µM, Namalwa cells were subjected to the WST-1 cell viability assay, showing no effect of AS1842856 on cell viability at 0.01 µM and a reduction in cell viability at 0.1 µM (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RAG1 and RAG2 are target genes of the transcription factor FOXO1 and inactivation of FOXO1 has been described to reduce expression of RAG1 and RAG2 (Lazorchak et al 2010 ; Lazorchak and Su 2011 ; Benhamou et al 2018 ; Peña-Pérez et al 2022 ). In order to study whether inhibition of FOXO1 also downregulates RAG1 and RAG2 expression in Namalwa cells, they were exposed to increasing concentrations (up to 0.1 µM) of the FOXO1 inhibitor AS1842856 for 6, 24 and 48 h. After exposure to 0.01 and 0.1 µM, Namalwa cells were subjected to the WST-1 cell viability assay, showing no effect of AS1842856 on cell viability at 0.01 µM and a reduction in cell viability at 0.1 µM (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism underlying the decreased expression of RAG genes upon treatment of Namalwa cells with PFASs is not clear. It is known that both RAG1 and RAG2 are target genes of FOXO1 and that inactivation of FOXO1 through induction of the PI3K-Akt signaling pathway results in decreased expression of the RAG genes (Lazorchak et al 2010 ; Lazorchak and Su 2011 ; Benhamou et al 2018 ; Peña-Pérez et al 2022 ). The hypothesis that the effect of PFASs on RAG expression in Namalwa cells is mediated by FOXO1 is corroborated by the finding that other immunological relevant genes downregulated by PFASs in Namalwa cells are also FOXO1 target genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the role of FOXO4 expression in B-cell development is unclear, evidence is emerging for the significance of FOXO3 , as FOXO3 -/- mice exhibit a loss of the pre-B cell population, and a reduction of B cells in the bone marrow (BM) and peripheral blood ( 58 ). Although the loss of FOXO1 impaired B cell lineage commitment, studies using a FOXO3 conditional deletion model demonstrated that FOXO3 deletion affected the production of LMPPs, CLPs and B-cell precursors ( 59 ). Furthermore, deletion of both FOXO1 and FOXO3 results in a complete block of CLP commitment towards the B-cell lineage ( 59 ).…”
Section: The Role Of the Foxo Family In B Cell Developmentmentioning
confidence: 99%
“…Although the loss of FOXO1 impaired B cell lineage commitment, studies using a FOXO3 conditional deletion model demonstrated that FOXO3 deletion affected the production of LMPPs, CLPs and B-cell precursors ( 59 ). Furthermore, deletion of both FOXO1 and FOXO3 results in a complete block of CLP commitment towards the B-cell lineage ( 59 ). These data shed light on the importance of FOXO3, in addition to FOXO1, in normal B-cell development and indicate a predominant switch of FOXO3 to FOXO1 expression is pivotal for B-cell lymphopoiesis ( Figure 2 ).…”
Section: The Role Of the Foxo Family In B Cell Developmentmentioning
confidence: 99%